Variasi Bahasa Pada Mahasiswa Prodi Pendidikan Bahasa dan Sastra Indonesia Uin Syarif Hidayatullah Jakarta Melalui Platfrom Whatsapp - Amimi, Sulvia Aisyah; Rinjani, Maulida Meisya (Nanggroe: Jurnal Pengabdian Cendikia, 2024)
Language is the most important interaction tool in people's lives to interact with other communities. In the linguistic aspect, there is often a diversity of languages in a society. This is due to the factors of a heterogeneous society. For this reason, the author raised the theme of language variation in this study. This research focuses on the variety of languages used by students of PBSI, UIN Jakarta in communicating with each other through the Whatsapp platform. Social media platforms, one of which is the digital communication media platform Whatsapp, can cause a community to experience language variations, namely through a variety of writing. In this study, the research method used was a qualitative descriptive method and the data collection technique carried out was to collect data through the Whatsapp Group of PBSI Students, then classified, analyzed and described. It can be concluded that the most common language variations used by PBSI Students are Mixed Codes, Slang, and Acronyms with a total of 19 data. Mix Code as much as 9 data, Slang as much as 5 data, and Acronyms as much as 5 data.